PHD SUPERVISION: AN EXPLORATORY AND A PRELIMINARY STUDY ABOUT THE SUPERVISOR POINT OF VIEW - Ribau, Isabel (PEOPLE: International Journal of Social Sciences, 2018)
It is well known that PhD attrition is high, and that is a problem for higher education systems, but also to the society. The scientific and technological development (the research enterprise) of a society is intimately related to the knowledge that is developed and produced in higher education systems. The attrition is an obstacle to science and technology improvements since students don’t develop and conclude their research project, which would bring new knowledge to society. From the students’ point of view, this attrition has personal but also financial and career consequences. On opposite side is the excellence in supervision, which reduce attrition, promote a holistic formation of the students, as a person and as a researcher, and is a facilitator of learning and a sponsor of knowledge. There are few studies in Portugal related to the third cycle, and fewer related to supervision practices and experience. In this context and trying to identify the supervision practices and experience lived by the PhD students and supervisors, an exploratory survey regarding PhD supervision was developed, applied to Science Education PhD students and supervisors and analysed. Based on this exploratory study we developed another more extensive one - a preliminary survey- that was applied to Universidade Nova de Lisboa students and supervisors. In this paper, we will present the results related to supervisors. The results from the two populations have significant differences related to the socialization/integration process in the research area, but above all it was not possible to perceive how supervisor monitor and evaluated the research process and progress.